Social Entrepreneurship as Driver for Increasing Social Innovation - Antoniuk, D.; Bui, Yu.; Berezhnytska, U.; Savko, O.; Hobyr, I. (Science and Innovation, 2023)
Introduction. One of the directions of strengthening the social component in the context of sustainable development is the spread of social innovations. The processes of generation and production of innovations should be considered through activating social development, innovating activity of enterprises, and social entrepreneurship that primarily focuses on achieving a social effect in society. Problem Statement. It is expedient to activate the development of social innovations based on a detailed study of the prerequisites through regional programs to support social entrepreneurship, taking into account the resource capabilities and peculiarities of the functioning of the regions. Social entrepreneurship generates economic, environmental, and social values. Purpose. Research the prerequisites, problems, and prospects for the development of social entrepreneurship as one of the drivers of the activation of social innovations in the conditions of modern geopolitical and socioeconomic challenges. Material and Methods. There have been used the methods of analysis, synthesis, comparison, structural, functio nal, system, statistical analysis, and integration. Results. The results of monitoring the activities of social enterprises in the EU countries have been analyzed. The prerequisites and trends of the development of innovative and social entrepreneurship in Ukrainian territories have been studied based on the proposed integral index of the ability of regions to do social entrepreneurship and socially responsible and innovating business. Conclusions. The importance of social entrepreneurship in solving social needs in the country and activating social innovations has been proven. Geopolitical, socio-economic, and institutional challenges of recent years have become a powerful impetus for the activation of social entrepreneurship in Ukraine.